Mining elements of siderophore chirality encoded in microbial genomes. Issue 1 (28th November 2022) - Butler, Alison; Jelowicki, Aneta M.; Ogasawara, Haley A.; Reitz, Zachary L.; Stow, Parker R.; Thomsen, Emil
Abstract : The vast majority of bacteria require iron to grow. A significant iron acquisition strategy is the production of siderophores, which are secondary microbial metabolites synthesized to sequester iron(III). Siderophore structures encompass a variety of forms, of which highly modified peptidic siderophores are of interest herein. State‐of‐the‐art genome mining tools, such as antiSMASH (antibiotics & Secondary Metabolite Analysis SHell), hold the potential to predict and discover new peptidic siderophores, including a combinatoric suite of triscatechol siderophores framed on a triserine‐ester backbone of the general class, (DHB‐ l /d CAA‐ l Ser)3 (CAA, cationic amino acid). Siderophores with l /d Arg, l /d Lys and l Orn, but not d Orn, were predicted in bacterial genomes. Fortuitously the d Orn siderophore was identified, yet its lack of prediction highlights the limitation of current genome mining tools. The full combinatoric suite of these siderophores, which form chiral iron(III) complexes, reveals stereospecific coordination chemistry encoded in microbial genomes. The chirality embedded in this suite of Fe(III)‐siderophores raises the question of whether the relevant siderophore‐mediated iron acquisition pathways are stereospecific and selective for ferric siderophore complexes of a defined configuration. Abstract : The genome mining tool antiSMASH is leveraged to make de novo structural predictions for a combinatoric suite of triscatechol siderophores framed on an oligo serine ester backbone with the d ‐ and l ‐cationic amino acids (CAA) Arg, Lys and Orn. The stereochemistry of the CAA directs the chirality of the Fe(III)‐siderophore complex, revealing stereospecific coordination chemistry encoded in microbial genomes.